Divorcing Husbands as a Solution to Protect Women’s Dignity: A Case Study of Domestic Violence at Madura Religious Court - Musawwamah, Siti (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This present study is concerned with the domestic violence settlements in divorce cases at religious courts. The study aimed to investigate the underlying reasons behind filing a divorce to religious courts, the women’s position in the trial process, and the women’s access to justice, as well as the women’s acceptance of the decisions of domestic violence cases. This case study collected the primary data through documents and interviews. The documents were court decisions concerning domestic violence, and the interviewees consisted of judges and domestic violence victims. The findings of the study found that resolving domestic violence through a judicial divorce in a religious court has been more practical and less complicated, which only involves limited parties, with an aim to preserve the family’s reputation (marwah) and children’s psychology. Further, women have the same legal standing as their husbands during the trial process, but this does not guarantee post-divorce justice because the husbands rarely attend court hearings (i.e., verstek decision). Women, the victims of domestic violence who resolve the violence through a divorce, accept the decision of the panel of judges even though the judges only grant the primary lawsuit to terminate the marriage bond. For these women, the decision is seen as a solution that can break the chain of violence and tyrannical behavior of their husbands. The urge to be immediately free of the snares of violence causes them to overlook the various risks of divorce, such as becoming widows and bearing all of the obligations that are not theirs, e.g., caring for and fulfilling all of their children’s needs on their own.